Congenital right ventricular diverticulum: An atypical presentation - Debasis Das; Nilanjan Dutta; Arya Kamal Das; Manish Kumar Sharma; Rangan Koley; Amitabha Chattopadhyay; Sanjiban Ghosh; Shubhadeep Das (Wolters Kluwer Medknow Publications, 2020)
Congenital ventricular diverticulum is a rare congenital malformation of the heart. It remains mostly asymptomatic unless associated with other congenital cardiac defects. We present a case of a 4-month-old child who had dextrocardia, large inlet ventricular septal defect, amounting to single ventricle, and severe pulmonary artery hypertension. There was a right ventricular diverticulum which passed through the foramina of Morgagni to give rise to a pulsating lump in the epigastrium. Right ventricular diverticulum presenting with a pulsating mass in the abdomen is a rare entity. The confirmation of diverticulum was made with histopathology.